1998
DOI: 10.1037/0021-9010.83.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Predicting voice behavior in work groups.

Abstract: This field study of 441 full-time employees in 95 work groups examined voice behavior (constructive challenge to the status quo with the intent of improving the situation rather than merely criticizing) as a function of person-centered (satisfaction with the work. group, global self-esteem) and situational factors (group size, self-managed vs. traditional style of management). Using a measure of voice with demonstrated construct validity, the study showed that these person and situation factors explained 10% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
691
1
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 878 publications
(763 citation statements)
references
References 102 publications
24
691
1
9
Order By: Relevance
“…However, these results are overall small in size, and third variables could explain the results. In this vein, in the study by LePine and Van Dyne (1998), ethnicity correlated more strongly with education than it did with proactivity (r=.15, p>.01 for education, as opposed to r=.10, p>.05 for proactivity) in that non-white employees typically also possessed lower educational qualifications. These qualifications in their own right might explain the relationship between ethnicity and the level of engagement in proactive behaviors.…”
Section: Individual Antecedentsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, these results are overall small in size, and third variables could explain the results. In this vein, in the study by LePine and Van Dyne (1998), ethnicity correlated more strongly with education than it did with proactivity (r=.15, p>.01 for education, as opposed to r=.10, p>.05 for proactivity) in that non-white employees typically also possessed lower educational qualifications. These qualifications in their own right might explain the relationship between ethnicity and the level of engagement in proactive behaviors.…”
Section: Individual Antecedentsmentioning
confidence: 90%
“…(2001) found meta-analytical evidence of a positive relationship (r c =.12, p<.05) between educational background and the degree of proactive job search. In the same vein, in their research on voicing behavior in groups, LePine and Van Dyne (1998) found that individuals with a higher educational background were also more likely to speak out with suggestions for improvements (β=.13, p<.05).…”
Section: Individual Antecedentsmentioning
confidence: 91%
See 1 more Smart Citation
“…High self-esteem is manifest in enhanced initiative, happiness and life satisfaction (Buhrmester et al 1988, Diener & Diener 1995, LePine & Van Dyne 1998, Furnham & Cheng 2000. Self-esteem is positively associated with better self-rated health (Glendinning 1998), and low self-esteem has been related to poor physical health outcomes (Nirkko et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain the job creation and income generation, which deemed as the backbone of the Malaysian economy, we have to sustain SME development in Malaysia (June & Mahmood, 2011). LePine and van Dyne (1998) found that it is important of innovation in recent business environment situation and they encourage more researches that help to enhance our understanding of voice. In the research by Nikolaou et al (2008), they found that there is more and more important for an organization relies on employees who are willing to express their new ideas and make constructive suggestion for change in order to initiatively respond to the challenges of the business environment.…”
Section: Introductionmentioning
confidence: 99%